If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -4(1) = 7 Multiply -4 * 1 -2x + -4 = 7 Reorder the terms: -4 + -2x = 7 Solving -4 + -2x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -2x = 7 + 4 Combine like terms: -4 + 4 = 0 0 + -2x = 7 + 4 -2x = 7 + 4 Combine like terms: 7 + 4 = 11 -2x = 11 Divide each side by '-2'. x = -5.5 Simplifying x = -5.5
| 3+4t=35 | | 10-8x=54-36x | | 65-3x=6x+15 | | -2(0)-4y=7 | | 10-10x=88-24x | | 3x-10y=37 | | -38-8x=7x+22 | | (a-5)(2a+3)(a+5)= | | x^2+4x-121=0 | | 10+a=4 | | -32-2x=14-8x | | 11x+6=104 | | 6x+10=-38-10x | | 4x+2(3-x)=14 | | 11x-5=9x+3 | | (4x^3-3x+9)+(-2x^2-4)+(8x+3x^3)= | | 6x+19=16x-71 | | 165-6x=6x+9 | | -14-5x=14-9x | | 3x^2+9x-27=0 | | x^2-3x=1 | | (-7x^3)= | | 112-3x=15x+24 | | x^2*x^4*x= | | 10-8x=49-29x | | x^2+14x+4=0 | | 20x^2-33xy+10y^2=0 | | 2c+4(c+9)=6 | | 6d-7=5d+3 | | x+18=59 | | 7r=6(r-14) | | 13x+18=3x+308 |